Neurovascular retinal impairment in early-treated adults with phenylketonuria - Buonamassa, Rosa; Boscia, Giacomo; Gaudiomonte, Marida; Guerriero, Silvana; Fischetto, Rita; Montepara, Alfonso; Grassi, Maria Oliva; Pignataro, Maria Grazia; Puzo, Pasquale; Giancipoli, Ermete; D’addario, Marina; Alessio, Giovanni; et al. (Frontiers in Neurology, 2024)
Purpose To compare radial peripapillary capillary (RPC) vascular plexus parameters and peripapillary retinal nerve fiber layer (pRNFL) thickness between Early-Treated Adults with Phenylketonuria (ETPKU) and controls. Methods This observational study was a monocentric, case control study including 36 eyes of 36 participants. Among these, 18 were early-treated PKU (ETPKU) and 18 were controls. A SD-OCTA (XR Avanti AngioVue OCTA; Optovue Inc., Fremont, CA) was employed to assess the OCT and OCTA parameters of all the participants. The main outcome measures were the RPC vessels density (VD) %, and the pRNFL thickness. Results The average pRNFL thickness was significantly reduced in ETPKU (110.78 ± 12.48 μm) compared to controls (113.22 ± 13.95 μm), p = 0.046. The mean VD% of the small vessels of the RPC plexus was 52.31 ± 2.2 in ETPKU and 50.71 ± 3.2 in controls (p = 0.049), while the VD% of all the radial peripapillary capillary plexus (RPCP) was 58.5 ± 2.2 in ETPKU and 55.08 ± 3.4 in controls (p < 0.001). By contrast, there were no differences in age, sex, and IOP between the two groups. Conclusion Through structural OCT and OCTA, we observed thinning of the nerve fibers accompanied by an increase in perfusion of the RPC plexus. Thus, our conclusions suggest that OCTA may serve as a noninvasive method to identify novel retinal biomarkers in ETPKU.